Reposition Analysis Changes in The Policy of The National Exam Curriculum (UN) Into the Minimum Competency Assessment (AKM) And Character Survey Dunn Version - Sri Tubilah Noor (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Analysis of the repositioning of changes to the National Examination curriculum policy into a Minimum Competency Assessment and Character Survey. This analysis is an intellectual and practical activity to make assessments and communicate policies to obtain relevant information. The analysis of the change in UN policy to AKM and the Character Survey does not only analyze data and information, but also pays attention to all aspects that affect the process of making a policy, starting from analyzing problems, collecting information, determining policy alternatives to the delivery of these alternatives to policy makers. The approach in policy analysis uses a descriptive and normative approach. The descriptive approach aims to present information to decision makers, so that decision makers understand the problems that are being highlighted from a policy issue. While the normative approach aims to help decision makers to solve a policy. The evaluative approach, which explains what it is about the results of an effort made by an activity or program. The results of the policy analysis according to Dunn regarding the repositioning of Indonesian Curriculum Policy Changes in the National Examination into a Minimum Competency Assessment and Character Survey do not merely analyze data and information, but pay attention to all aspects related to the process of making a policy, starting from analyzing the problem, collecting information, analysis, determination of policy alternatives, to the delivery of these alternatives to decision makers. The purpose of policy analysis research, according to Dunn, is to explore whether an educational idea is realistic and enables educational policies to be implemented. In this research, it was found that the repositioning of changes to the national exam curriculum policy into a minimum assessment and a character survey of the change in the National Examination policy to AKM and the Character Survey had a lot of pros and cons as well as the impact felt by all parties.